Descriptions of new and known species of the superfamily Tylencholaimoidea (Nematoda: Dorylaimida) from Jammu & Kashmir, India (Journal of Nematode Morphology and Systematics, 2010)
Three new and three known species belonging to the superfamily Tylencholaimoidea are described and illustrated from Jammu & Kashmir State of India. Tylencholaimus pini sp. n. is characterized by having body 0.5-0.6 mm long, offset lip region, odontostyle 7-8 μm long, odontophore with slightly thickened base, expanded part of pharynx with gradual expansion, female genital system mono-prodelphic, vulva transverse, vagina with sclerotized walls, and short conoid tail with wrinkled terminus. Promumtazium indicum sp. n. is characterized by its body 0.91-1.14 mm long, lip region offset by constriction and 9.0-9.5 μm wide, stirrup-shaped amphids, odontostyle asymmetrical and 6 μm long, female genital system amphidelphic, spicules 37 μm long, two well spaced ventromedian supplements, and short conoid tail with bluntly rounded terminus. Proleptonchus sclerouterinus sp. n. is distinguished by having body 1.21-1.33 mm long, lip region low and offset by constriction, amphids cup-shaped and occupying almost entire corresponding body width, odontostyle 7.0 μm long, female genital system pseudo-monodelphic, pars dilatata uteri with distinctly sclerotized central lumen containing refringent apophyses, posterior genital branch with well developed uterus and sphincter followed by sac-like rudimentary oviduct, and hemispheroid tail with thick cuticle at terminus. Tylencholaimellus striatus Thorne, 1939, T. sayeedi Siddiqi, 1965 and T. eskei Siddiqi & Khan, 1964 are redescribed; male is reported for the fi rst time for T. eskei.